Cover Image. (5th May 2020) - Laniado, Nadia; Badner, Victor M.; Sanders, Anne E.; Singer, Richard H.; Finlayson, Tracy L.; Hua, Simin; Kaste, Linda M.; Isasi, Carmen R.
Abstract : The cover image is based on the Clinical Periodontology Social capital and periodontal disease in Hispanic/Latino adults in the United States: Results from the Hispanic Community Health Study/Study of Latinos by Nadia Laniado et al., https://doi.org/10.1111/jcpe.13262 .